(untitled) (Historia Agraria de América Latina, 2025)
In the first decades of the 20th century, various initiatives were undertaken to diversify the productive structure of the province of Mendoza, which had specialized in winemaking since 1890. This article addresses the evolution of malting barley cultivation in Mendoza between 1914 and 1935, employing information from Statistical Yearbooks of the province of Mendoza, agricultural magazines, newspapers, and legislative debates. We seek to identify business and state strategies for the development of malting and brewing activities within the framework of the drive for productive diversification in a predominantly wine-producing province, the impact of World War I and the Great Depression on the beer industry. We also analyze the evolution of barley plantations, identifying the main cultivation areas, in order to determine the scope of these initiatives for the development of the new agroindustrial activity. The main argument put forward is that, as part of its business strategies aimed at consolidating malt and beer production in different parts of the country, in Mendoza the Bemberg group made significant investments to develop the cultivation of malted barley and the production of malt and beer, thus achieving self-sufficiency in the supply of a fundamental input that until then had been imported.